Why did the Art of Writing Spread to the West? Reflexions on the Alphabet of Marsiliana (d’Albenga, Toscana) - Вundgård, J. A.
“Kodex” aus Elfenbein, ca. 650 v. Chr., ähnlich den Writing Boards aus Kalaḫ/Nimrud.